Firms Operating under Electricity Constraints in Developing Countries - Alby, Philippe; Dethier, Jean-Jacques; Straub, Stephane (Oxford University Press on behalf of the World Bank, 2014)
Many developing countries are unable to provide their industrial sectors with reliable electric power, with the result that many enterprises must contend with an insufficient and unreliable supply of electricity. Because of these constraints, enterprises often opt for self-generation of electricity even though it is widely considered a second-best solution. This paper develops a theoretical model of investment behavior in remedial infrastructure in the presence of physical constraints. It then illustrates the model's predictions using a large cross-country sample of enterprises from the World Bank Enterprise Survey database. Electricity-intensive sectors in high-outage countries are characterized by a significantly lower share of small firms.